2017
DOI: 10.5578/mb.46549
|View full text |Cite
|
Sign up to set email alerts
|

Production and Molecular Characterization of Plasmodium falciparum Recombinant Circumsporozoite Protein with 37 NANP and 4 NVDP Epitopes

Abstract: Malaria is caused by the protozoan parasite Plasmodium, the leading cause of death amongst the parasitic diseases. The disease is transmitted to human by the bites of female Anopheles mosquitoes. According to the World Health Organization (WHO) data, there were an estimated 214 million malaria cases and estimated 438.000 deaths occurred worldwide, in 2015. It is observed that 90% of all the deaths due to malaria occur in Africa. 78% of these cases were children who are under five years old. Intensive malaria i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…54 In children aged one to four years, RTS, S/AS02A substantially elicited anti-CSP IgG1 followed by IgG3 and IgG2. An analysis of a cohort (n = 195) of participants from the phase III RTS, S/AS01B vaccine study in young children (6)(7)(8)(9)(10)(11)(12) results, with a predominance of IgG1 and IgG3 responses. It was shown that vaccination-induced immunity was correlated with a larger ratio of cytophilic antibodies (IgG1 and IgG3) to non-cytophilic antibodies (IgG2 and IgG4).…”
Section: Biophysical and Structural Impact Of The Anti-pfcsp Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…54 In children aged one to four years, RTS, S/AS02A substantially elicited anti-CSP IgG1 followed by IgG3 and IgG2. An analysis of a cohort (n = 195) of participants from the phase III RTS, S/AS01B vaccine study in young children (6)(7)(8)(9)(10)(11)(12) results, with a predominance of IgG1 and IgG3 responses. It was shown that vaccination-induced immunity was correlated with a larger ratio of cytophilic antibodies (IgG1 and IgG3) to non-cytophilic antibodies (IgG2 and IgG4).…”
Section: Biophysical and Structural Impact Of The Anti-pfcsp Antibodiesmentioning
confidence: 99%
“… 8 This has been observed in a series of Phase I, III, and III clinical trials performed in many different populations including children, and infants, as young as 6 weeks of age. 9–11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation